An anti-sway positioning control method via load generalized position tracking with disturbance observer. (November 2020) - Niu, Dan; Zhu, Yuxuan; Chen, Xisong; Li, Qi; Wang, Xiaojun; Yang, Yanlan; Wang, Simin
The bridge crane system is widely used in the industrial production for transporting large loads. Its anti-sway positioning control is quite crucial for enhancing handling efficiency and safety, but it is also difficult due to underactuated dynamics and various disturbances. In this paper, an anti-sway positioning control algorithm for unmanned crane is proposed based on the load generalized position tracking control algorithm (GPTC), which combines with a disturbance observer to effectively reject the lumped disturbances. The test results show that the proposed method can effectively achieve anti-sway and positioning with prominent disturbance suppression improvements.